Juridical Study of the Concept of Maqashid Shariah in Inheritance Law in Indonesia - Ali Sam'un; Fauzan (Yayasan Multidimensi Kreatif, 2024)
Inheritance law is an important part of Islamic law that aims to maintain justice and family welfare. This study aims to analyze the application of the concept of sharia maqashid in inheritance law in Indonesia, focusing on evaluating the conformity between the principles of sharia maqashid and applicable inheritance law regulations, such as the Compilation of Islamic Law (KHI) and customary law practices. The approach used is a juridical normative study with primary data analysis from the Qur'an, Hadith, and laws, as well as secondary data in the form of literature and related case studies. This research is expected to provide an in-depth picture of how the principles of sharia maqashid can strengthen justice and benefits in the distribution of inheritance. The results of the study show that inheritance law in Indonesia still faces challenges in harmonizing between Islamic, customary, and national law. Sharia maqashid principles, such as the protection of property (hifz al-mal) and descendants (hifz an-nasl), are often not fully accommodated in the implementation of inheritance law. Although the KHI has attempted to accommodate Islamic law, differences in interpretation and customary influences often lead to inconsistencies with the main purpose of sharia maqashid. In some cases, the distribution of inheritance actually creates conflicts that are contrary to the principles of justice and family welfare. This study recommends inheritance law reform in Indonesia with a maqashid-based approach to sharia to ensure harmony between positive law, custom, and Islamic principles. This effort can be carried out through policy revisions, increasing the socialization of sharia maqashid, and empowering the community in understanding the importance of justice in inheritance law. Thus, inheritance law in Indonesia can be more oriented towards achieving sharia goals in protecting individual rights and creating harmony in society.